2014
DOI: 10.3109/09537104.2014.987225
|View full text |Cite
|
Sign up to set email alerts
|

Use of allogeneic stem cell transplantation for moderate–severe Glanzmann thrombasthenia

Abstract: Glanzmann thrombasthenia (GT) is a rare, autosomal recessive coagulopathy characterized by either qualitative or quantitative abnormalities of the membrane glycoprotein αIIbβ3 complex leading to bleeding tendencies, ranging from purpura to life-threatening hemorrhage. Although patients can be managed with supportive measures including platelet transfusions, complications such as alloimmunization are possible. Allogeneic stem cell transplantation (ASCT) can be indicated in severe cases of GT. We report the case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Furthermore, we used myeloablative conditioning (MAC), which results in faster implantation, better reconstruction of the hematopoietic system, and lower transplant-related infections, compared with reduced intensity conditioning (RIC). Walz et al (10) reported an 8-month-old GT patient who underwent a successful matched sibling donor transplantation using reduced intensity conditioning, and neutrophils and platelets were implanted at +18 post-transplantation, later than in the current patient (+11 post-transplantation). Connor et al (11) reported a case of GT who underwent reduced intensity conditioning, and the chimerism rate was only 30%.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, we used myeloablative conditioning (MAC), which results in faster implantation, better reconstruction of the hematopoietic system, and lower transplant-related infections, compared with reduced intensity conditioning (RIC). Walz et al (10) reported an 8-month-old GT patient who underwent a successful matched sibling donor transplantation using reduced intensity conditioning, and neutrophils and platelets were implanted at +18 post-transplantation, later than in the current patient (+11 post-transplantation). Connor et al (11) reported a case of GT who underwent reduced intensity conditioning, and the chimerism rate was only 30%.…”
Section: Discussionmentioning
confidence: 97%
“…However, the treatments described here may not be adequate for severe cases of GT, which may require the use of recombinant factor VIIa [2]; in such cases, the only cure for GT is allogeneic hematopoietic stem cell transplantation. While HSCT has been successfully performed in adult patients with GT, its application is more successful when administered during childhood [3,4]. Considering the risks associated with HSCT among adults, Cid et al [5] recommended that physicians and their patients complete a cost-bene t analysis to determine bleeding risks and the ability to control recurrent bleeding, prior to transplant approval for adults.…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic hematopoietic stem-cell transplantation (HSCT) is considered a curative treatment for this disease, but a balance must be struck between the morbidity-mortality of transplantation and its benefits. To date, several patients with GT have been successfully transplanted [6][7][8][9][10][11][12][13][14][15][16]. Remarkably, all these patients were children, except for one adult patient with GT who underwent HSCT due to a concomitant diagnosis of acute myeloblastic leukemia [11,17].…”
Section: Introductionmentioning
confidence: 99%